Effect of Methane Inhibitors on Ruminal Microbiota During Early Life and Its Relationship With Ruminal Metabolism and Growth in Calves - Cristobal-Carballo, Omar; McCoard, Susan A.; Cookson, Adrian L.; Ganesh, Siva; Lowe, Katherine; Laven, Richard A.; Muetzel, Stefan (Frontiers in Microbiology, 2021)
The present study aimed to determine whether dietary supplementation with methanogen inhibitors during early life may lead to an imprint on the rumen microbial community and change the rumen function and performance of calves to 49-weeks of rearing. Twenty-four 4-day-old Friesian x Jersey cross calves were randomly assigned into a control and a treatment group. Treated calves were fed a combination of chloroform and 9,10-anthraquinone in the solid diets during the first 12 weeks of rearing. Afterwards, calves were grouped by treatments until week 14, and then managed as a single group on pasture. Solid diets and water were offered ad libitum. Methane measurements, and sample collections for rumen metabolite and microbial community composition were carried out at the end of weeks 2, 4, 6, 8, 10, 14, 24 and 49. Individual live weight (LW) and dry matter intake (DMI) were regularly monitored over the duration of the experiment. Methane emissions decreased up to 90% whilst hydrogen emissions increased in treated compared to control calves, but only for up to two weeks after treatment cessation. The near complete methane inhibition did not affect calves’ DMI and growth. The acetate:propionate ratio decreased in treated compared to control calves during the first 14 weeks but was similar at weeks 24 and 49. The proportions of Methanobrevibacter and Methanosphaera decreased in treated compared to control calves during the first 14 weeks; however, at week 24 and 49 the archaea community was similar between groups. Bacterial proportions at the phylum level and the abundant bacterial genera were similar between treatment groups. In summary, methane inhibition increased hydrogen emissions, altered the methanogen community and changed the rumen metabolite profile without major effects on the bacterial community composition. This indicated that the main response of the bacterial community was not a change in composition but rather a change in metabolic pathways. However, when methane inhibition ceased, the methanogen community, rumen metabolites and hydrogen emissions were similar between treatment groups, indicating that it is not possible to imprint a low methane microbiota into the rumen when treatments are only offered in the solid feed of pre-weaned calves.